1999
DOI: 10.1190/1.1444665
|View full text |Cite
|
Sign up to set email alerts
|

An improved method of determining near‐surfaceQ

Abstract: We performed field measurements using the modified method of spectral ratios to estimate shallow seismic Q. Three component seismograms from artificial sources were recorded to determine [Formula: see text] and [Formula: see text] in the unconsolidated sedimentary layer at the experimental site. This modified spectral ratio method was assumed to be frequency dependent, and the amplitude ratios then were plotted against the arrival‐time difference of any two receivers for one particular frequency. The slope of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…In his work, Q was independent of frequency. Although some authors suggest that near-surface Q may be frequency dependent (Jeng et al, 1999), Xia et al (2002) followed the laboratory results (Johnston, 1981) and Mitchell's work (1975) that Q is independent of frequency, allowing determination of Q as a function of depth based on amplitude attenuation of Rayleigh-wave data. The quality factor Q as a function of depth, which is directly related to the material damping ratio D (= 0.5Q − 1 ) (Lai and Rix, 1998;Rix et al, 2000), is of fundamental interest in earthquake engineering (Kramer, 1996), geotechnical engineering, ground-water, and environmental studies, as well as in oil exploration and earthquake seismology.…”
Section: Introductionmentioning
confidence: 96%
“…In his work, Q was independent of frequency. Although some authors suggest that near-surface Q may be frequency dependent (Jeng et al, 1999), Xia et al (2002) followed the laboratory results (Johnston, 1981) and Mitchell's work (1975) that Q is independent of frequency, allowing determination of Q as a function of depth based on amplitude attenuation of Rayleigh-wave data. The quality factor Q as a function of depth, which is directly related to the material damping ratio D (= 0.5Q − 1 ) (Lai and Rix, 1998;Rix et al, 2000), is of fundamental interest in earthquake engineering (Kramer, 1996), geotechnical engineering, ground-water, and environmental studies, as well as in oil exploration and earthquake seismology.…”
Section: Introductionmentioning
confidence: 96%
“…The Q model is assumed to be frequency independent (Kjartansson, 1979;Wang and Guo, 2004), but could be frequency dependent in practice (Jeng et al, 1999). Defining a single variable χ ≡ ωτ, equation 1 can be rewritten asĀ…”
Section: Stable Q-analysis Methodsmentioning
confidence: 99%
“…Vassiliou et al (1982) found the Q S /Q P ratio equal to unity for air dry rocks and less than unity for fully saturated rocks. Although some authors suggest that near-surface Q may be frequency dependent (Jeng et al 1999), Xia et al (2002) followed the laboratory results (Johnston 1981) and Mitchell's work (1975) that Q is independent of frequency, allowing determination of Q as a function of depth based on the amplitude attenuation of Rayleigh-wave data.…”
Section: Introductionmentioning
confidence: 99%